Access to Recovery and Recidivism Among Former Prison Inmates. (June 2017) - Ray, Bradley; Grommon, Eric; Buchanan, Victoria; Brown, Brittany; Watson, Dennis P.
Access to Recovery (ATR) is a Substance Abuse and Mental Health Services Administration (SAMHSA)–funded initiative that offers a mix of clinical and supportive services for substance abuse. ATR clients choose which services will help to overcome barriers in their road to recovery, and a recovery consultant provides vouchers and helps link the client to these community resources. One of ATR's goals was to provide services to those involved in the criminal justice system in the hopes that addressing substance abuse issues could reduce subsequent criminal behaviors. This study examines this goal by looking at recidivism among a sample of clients in one state's ATR program who returned to the community after incarceration. Results suggest that there were few differential effects of service selections on subsequent recidivism. However, there are significant differences in recidivism rates among the agencies that provided ATR services. Agencies with more resources and a focus on prisoner reentry had better recidivism outcomes than those that focus only on substance abuse services.